1657, Va. Acts 437, Act 13 - (:unkn) unknown (General Publisher, 1657)
If any planter or person shall hunt or shoot upon or within the limits or precincts of his neighbor or others’ dividends without leave first obtained for his so doing and having been warned by the owner of the land, to forbear hunting and shooting as aforesaid: He or they so offending shall forfeit for every such offense four hundred pounds of tobacco . . .
--
Keywords: HUNTING; DISCHARGE